Education Without Boundaries: Bojonegoro Regency Government's Efforts to Expand Access for People with Disabilities - Anis Saidah; Ali Mudlofir (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the efforts of the Bojonegoro Regency Government in expanding access to education for people with disabilities through the Education Without Borders policy, which is oriented towards inclusive development and social justice. The main problem identified is the limited physical, social, and economic accessibility for people with disabilities to obtain adequate educational services. This study uses a descriptive qualitative method with a case study approach, through in-depth interviews with officials from the Education Office, Social Services Office, Transportation Office, organizations for people with disabilities (PPDI and HWDI), as well as direct observation in inclusive schools and public facilities. The results show that the Bojonegoro Regency Government has committed to expanding access to education through various initiatives such as providing free transportation for students with disabilities, adding inclusive schools, training special assistant teachers, and building disability-friendly public facilities. The inclusive transportation program has been proven to increase the attendance rate of students with disabilities by up to 35%, reduce the dropout rate, and strengthen student self-confidence. However, limitations in fleets, human resources, and inter-agency coordination remain major obstacles in policy implementation. Overall, the Education Without Borders policy in Bojonegoro has demonstrated effective inclusive governance practices and can be used as a national model for other regions in expanding access to inclusive education based on social justice.